Santri, Kelas Menengah dan Politik Lokal Indonesia - Yulion Zalpa (Fakultas Adab dan Humaniora UIN Raden Fatah, 2017)
This journal means to give an ilustration function and role of santri, as part of middle class people in Indonesia. The result of this journal shows that political dynamics of santri as the middle class always changes in every era. In colonialism era, a group of santri unite to take an independence. Meanwhile, a group of santri in post-independence era want to dominate with an idea to make Islam as the rules of nation and the government must take the policy to limit it. Consequently, a group of santri show more in practical politics in government and the other strategic position in reformation era. However, the identity of group of santri more dissolved by the interest group and another as a result from their position as middle class. Therefore, the role and identity of a group of santri as middle class show the shortage whwn the differences interest and interference of outsider precisely cause the dissension in that group of santri. Keyword : santri, middle class, politic.